Growth of carbon dots in nanoporous silica glasses for highly enhanced dual-wavelength emission. Issue 3 (21st December 2022) - Ma, Yunxiu; Ke, Xianzhi; Liu, Haolin; Pan, Jinyang; Ji, Zijuan; Li, Sha; Li, Jie
Abstract : Solid-state carbon dots (CDots) have great potential applications in photonics and optoelectronic devices due to their excellent optical properties, such as broad absorption bands, and tunable photoluminescence wavelengths. Abstract : Solid-state carbon dots (CDots) have great potential applications in photonics and optoelectronic devices due to their excellent optical properties, such as broad absorption bands, and tunable photoluminescence wavelengths. However, owing to the aggregation-induced quenching and thermal quenching effect, it is a challenge to achieve strong luminescent solid-state CDots with excellent thermal stability. Herein, solid-state CDots were designed and fabricated using a triple confinement nanoporous glass. The triple confinement in nanoporous glass by a highly rigid network, stable covalent bonding, and 3D spatial restriction efficiently inhibited the Föster resonance energy transfer of the CDots in the solid-state and highly confined the CDots in the nanopores and nanochannels of the nanoporous glass. The as-designed triple confined solid-state CDots exhibit dual emission wavelengths at 448 nm and 638 nm, 51 times enhanced photoluminescence intensity, and exceptional thermal stability up to 400 °C. This work provides design principles and a universal strategy to construct dual emission fluorescence materials with high photoluminescence intensity, and high thermal stability for promising applications.